The Impact of Economic Conditions on Social Assistance Programs and Poverty Alleviation - Simangunsong, Humala; Sihotang, Demita (Law and Economics, 2023)
Poverty remains a pervasive global challenge, necessitating effective policy interventions to uplift vulnerable populations. This research delves into the dynamic relationship between social assistance programs and poverty alleviation. Employing a mixed-methods approach, we investigate the impact of these programs on poverty rates, program effectiveness variations, demographic disparities, and the interplay with economic conditions. Our findings offer compelling insights. Firstly, social assistance programs exhibit a statistically significant reduction in poverty rates among beneficiaries, confirming their vital role in poverty alleviation. Moreover, variations in program effectiveness emerge, with cash transfer programs demonstrating immediate impact compared to in-kind assistance programs. Demographic differences further shape program outcomes, as programs targeting children and single-parent households exhibit pronounced effects on poverty reduction. Economic conditions also matter, as these programs prove more effective during periods of robust economic growth, serving as vital safety nets during economic downturns. Conditional social assistance programs demonstrate promise by incentivizing positive behaviors such as education enrollment and healthcare utilization. These findings hold significant policy implications, emphasizing the need for evidence-based program design and implementation. This research concludes with a call for comprehensive approaches to poverty alleviation, considering demographic variations, economic contexts, and the potential benefits of conditional programs. Ongoing monitoring and evaluation are pivotal in adapting programs to evolving circumstances, thus contributing to a more equitable and prosperous society.